Construction Of Telemedicine Health Data In Hospitals Based On Health And Personal Data Protection Laws - Nainggolan, Indra Lorenly; Tobing, Clara Ignatia; Nisa, Putri Ginatun (JURNAL HUKUM PELITA, 2024)
The basis of this research is that hospitals must implement a hospital health data information system, including telemedicine health data. These provisions are regulated in Law Number 17 of 2023 about Health. Existing norms still need to be clarified because there are no further regulations in the health law regarding hospital health data specifically for telemedicine health data protection. Meanwhile, Law Number 27 of 2022 about Personal Data Protection explains that health data is protected. At this point, legal construction is necessary to understand the health data of hospital telemedicine patients, which is an essential part of the health omnibus law. A comprehensive idea of what hospital telemedicine health data means is needed. The research method used is normative juridical, analyzing statutory regulations using conceptual and statutory approaches. The research results are that the concept of hospital telemedicine health data developed using technology must have legal protection. Norms governing hospital telemedicine health data should not harm patients. Meanwhile, there is no order to delegate regulation to statutory regulations under the law regarding telemedicine health data in the Health Law. In this context, it is necessary to interpret hospital telemedicine health data as national health information protected by the state.